2019
DOI: 10.1364/osac.2.000314
|View full text |Cite
|
Sign up to set email alerts
|

Compensating chirp of attosecond X-ray pulses by a neutral hydrogen gas

Abstract: It is demonstrated by numerical simulations that the attosecond chirp of high order harmonic pulses in the 530 to 1000 eV range can be partially compensated by the negative group delay dispersion of unionized molecular hydrogen gas. The transmission of X-rays through gas with the required pressure-length product for optimum chirp compensation is higher than 10% in the photon energy range that covers the K-edge of oxygen and Ledges of iron, cobalt, and nickel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…It is, however, difficult to compensate atto-chirp above the carbon K-edge (282 eV) due to the lack of materials that exhibiting negative group velocity dispersion and low loss. It was illustrated theoretically that attochirp in the 300-1000 eV range can be reduced by hydrogen gas or plasma with the proper pressure-length product given that the transmission of the gas or plasma is higher than 10% 51,52 .…”
Section: Isolated Water Window X-ray Attosecond Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, difficult to compensate atto-chirp above the carbon K-edge (282 eV) due to the lack of materials that exhibiting negative group velocity dispersion and low loss. It was illustrated theoretically that attochirp in the 300-1000 eV range can be reduced by hydrogen gas or plasma with the proper pressure-length product given that the transmission of the gas or plasma is higher than 10% 51,52 .…”
Section: Isolated Water Window X-ray Attosecond Pulsesmentioning
confidence: 99%
“…The transmission of ionized H 2 is even better. Single-atom simulations based on the strong-field approximation [54][55][56][57][58] of high-harmonic generation have been performed to demonstrate feasibility of the atto-chirp compensation in the 300-500 eV 51 and 530-1000 eV 52 photon energy regions. It has been shown that isolated attosecond pulses as short as 25-as are achievable when high-harmonic generation in helium is driven by single-cycle lasers centered at 1.7 μm or 3.2 μm.…”
Section: Isolated Water Window X-ray Attosecond Pulsesmentioning
confidence: 99%
“…Recently, attosecond X-ray pulses reaching the carbon K-edge (282 eV) have been produced by driving high harmonic generation with short-wave infrared lasers [ 12 , 13 , 14 , 15 ]. To generate single isolated attosecond pulses, various gating techniques [ 16 , 17 ] and chirp compensation methods [ 18 , 19 ] have been developed. Some of them have been implemented in generating isolated water window X-ray pulses around 50-attosecond pulse width [ 12 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the pioneer research, the dispersion of various materials are investigated in the XUV region, [26] and near Fourier transform limited pulses can be obtained with Xe [26] or Sn [27,28] as the dispersion compensation material for the spectral window of 150-300 eV. Hydrogen plasma [29] and neutral hydrogen [30] are proposed to be capable of compensating the atto-chirp in 300-500 eV and 500-1000 eV, respectively, which benefits the IAP generation with MIR drivers. With 800 nm driving pulses, the shortest IAP reported so far was 67 as, [5] and Zr foil was employed as the compensation material.…”
mentioning
confidence: 99%